2001
DOI: 10.1002/prot.10027
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of protein ionization equilibria with conformational sampling: pKa of a model leucine zipper, GCN4 and barnase

Abstract: The use of conformational ensembles provided by nuclear magnetic resonance (NMR) experiments or generated by molecular dynamics (MD) simulations has been regarded as a useful approach to account for protein motions in the context of pK(a) calculations, yet the idea has been tested occasionally. This is the first report of systematic comparison of pK(a) estimates computed from long multiple MD simulations and NMR ensembles. As model systems, a synthetic leucine zipper, the naturally occurring coiled coil GCN4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 62 publications
1
57
2
Order By: Relevance
“…Various protocols combining calculations of ionization equilibria with simulated protein flexibility have been elaborated. In different approaches, the considered structural changes rank from involving only polar hydrogen atoms (18,19,30,33), to side-chain fluctuations (31,32,34,35,38), to global structural motions (6,23,28,(39)(40)(41)(42). Overall, pK values from MD ensemble averages were closer to the experimental values in most cases.…”
Section: Conformational Flexibilitymentioning
confidence: 84%
See 1 more Smart Citation
“…Various protocols combining calculations of ionization equilibria with simulated protein flexibility have been elaborated. In different approaches, the considered structural changes rank from involving only polar hydrogen atoms (18,19,30,33), to side-chain fluctuations (31,32,34,35,38), to global structural motions (6,23,28,(39)(40)(41)(42). Overall, pK values from MD ensemble averages were closer to the experimental values in most cases.…”
Section: Conformational Flexibilitymentioning
confidence: 84%
“…Multiple shorter MD trajectories (starting from the same initial structure) might be superior to a single MD trajectory of the same total length (41). (iii) The initial structure is likely to influence the results of continuum pK predictions (23), although this is not always the case (43).…”
Section: Conformational Flexibilitymentioning
confidence: 99%
“…We will show below that protein permittivity cannot be used as parameter at ΔG el calculations, either. An alternative approach is to collect conformations using simulation methods such as molecular dynamics [3,5,9,14,22,26,27,28].…”
Section: Conformational Flexibility and Salt Bridge Dynamicsmentioning
confidence: 99%
“…A few studies have also tested to increase the sampling by starting from different structures, e.g. from different crystal structures or NMR ensembles [17,25,26,27,28], or even from structures generated by an initial conformational search [25]. Recently, we have also shown that the agreement of calculated and measured order parameters is improved if the MD simulations are started from different structures obtained from conformational disorder available in the crystal structures [18].…”
Section: Introductionmentioning
confidence: 99%